Methionine and its derivatives in dairy cow nutrition: implications for intestinal barrier function, periparturient performance, and metabolic health - Huo, Wenying; Lin, Yiyu; Wang, Cailing; Deng, Hongyu (Frontiers in Veterinary Science, 2025)
The increasing demand for high-quality protein products has driven substantial progress in dairy cow nutrition, with a focus on optimizing amino acid supply to enhance productivity and health. Methionine (Met), a key essential amino acid, plays multifaceted roles in supporting growth, lactation, and reproduction, as well as maintaining metabolic and immune homeostasis in ruminants. Recent evidence highlights the regulatory potential of dietary Met—particularly in its rumen-protected form (RPM)—on intestinal integrity and systemic metabolic function in dairy cows. This review provides a comprehensive synthesis of the molecular properties and functional roles of Met and its derivatives in ruminant physiology. We evaluate current research on Met’s influence on the microbial, chemical, mechanical, and immunological components of the intestinal barrier, as well as its effects on milk synthesis, reproductive performance, and metabolic modulation during the periparturient period. While the benefits of Met supplementation are well-recognized, critical knowledge gaps remain regarding its mechanisms of action, interactions with gut microbiota, optimal dosing strategies, individual variability in response, and long-term outcomes across lactations. To address these gaps, future studies should adopt integrative multi-omics and microbiota-metabolite profiling approaches, develop precision nutrition models, and explore synergistic interactions with other nutrients. Advancing our understanding of Met’s roles in dairy cow nutrition will support the development of targeted supplementation strategies aimed at improving gastrointestinal health, reproductive efficiency, and overall productivity in commercial dairy systems.